Effects of a single Pilates session on anxiety levels: Where you practice matters: Pilates and anxiety - C. Borges, Cezimar; A. Silva, Weder; M. Alves, Polissandro; Roberta dos Santos, Patrícia; F. Souza, Rebeca; do P. Lemes, Uitairany; de S. Romeiro, Amanda Maria (Manual Therapy, Posturology & Rehabilitation Journal, 2026)
Background: Anxiety are among the most common mental disorders across different populations. Objective: This study aimed to evaluate the effects of a single Pilates session on anxiety symptoms in two different practice environments. Method: The sample included 26 individuals, divided into two groups: Outdoor Pilates (OP, n = 9) and Studio Pilates (SP, n = 17). Each session lasted approximately 50 minutes and comprised a warm-up, followed by mobility and muscle-strengthening exercises using dynamic and static movements targeting the upper and lower limbs as well as the trunk. Anxiety "state" was assessed using the State-Trait Anxiety Inventory (STAI-S). Results: Mean anxiety scores decreased in both the OP group (∆% = –33.1, d = 1.41) and the SP group (∆% = –17, d = 0.72). A positive correlation was observed between recent distress and pre-session anxiety levels (Pearson’s r = 0.70, R² = 0.489), while a negative correlation was found between habitual physical activity and anxiety (Pearson’s r = –0.543, R² = 0.294), both statistically significant at p < 0.01. Conclusion: A single Pilates session, whether conducted outdoors or in a studio, positively impacts anxiety levels in adults. However, the reduction in anxiety was more pronounced in the outdoor environment, suggesting greater effectiveness in natural settings.